Pemberdayaan Masyarakat Melalui Home Industry Tempe dalam Meningkatkan Kemandirian Ekonomi Keluarga - Siti Maisita; Hidayatullah Haila; Herlina Siregar (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
Community empowerment is the provision of knowledge and encouragement for the community to have the ability to utilize their potential for a better quality of life. This study aims to determine Community Empowerment through Tempe Home Industry in Increasing Family Economic Independence, to examine the process of implementing this research to examine the problems (1) Community Empowerment Process through Tempe Home Industry in Increasing Family Economic Independence in Sukamanah Village, Parung Panjang Village, (2) Results of Community Empowerment through Tempe Home Industry in Increasing Family Economic Independence in Sukamanah Village, Parung Panjang Village, (3) Supporting and Inhibiting Factors of Community Empowerment through Tempe Home Industry in Increasing Family Economic Independence in Sukamanah Village, Parung Panjang Village. The method used by the author in this research is descriptive with a qualitative approach, where data is obtained from observations, interviews and documentation. The data source of this research consisted of 14 people, namely 7 managers of the tempe home industry and 7 members of the tempe home industry. The results showed that (1) The process of community empowerment through the tempe home industry has been carried out well, with a plan that has been prepared in advance. (2) The results of community empowerment through the tempe home industry are increased family economic independence such as responsibility, autonomy, initiative and self-control. (3) the supporting factors in the implementation of empowerment are human resources, high motivation, and the existence of government policies. There are obstacles such as the attitude of society that is still traditional, limited capital and the late development of science and technology. Suggestions in this study that managers are able to provide guidance in marketing products and members are able to increase the abilities obtained so that they can build a business independently. The result of this research is that the empowerment process runs according to the indicators of empowerment so that there is an increase in family economic independence.